Pengaruh Kesadaraan Wajib Pajak, Pelayanan Fiskus, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Widyana, Dewa Putu Gede; Wijana Asmara Putra, I Nyoman (E-Jurnal Akuntansi; Vol 30 No 1 (2020), 2020)
Taxpayer’s compliance is a form of compliance and responsibility of taxpayers to their obligations. This study aims to obtain evidence regarding the factors that influence taxpayer compliance, especially motor vehicle taxpayers registered in the Kantor Bersama Samsat Kota Denpasar. The study population was 393,598. The sample is determined by purposive sampling method, the amount of which is obtained by the Slovin formula so as to obtain as many as 100 respondents. Data were analyzed using multiple linear regression. The research obtained results that awareness of taxpayers, tax services, and tax sanctions had a positive influence on the level of taxpayer compliance in motorized vehicles in the Kantor Bersama Samsat Kota Denpasar . Keywords :  Compliance, Awareness, Fiskus, Tax Sanctions.